Vaccination status as a criterion for prioritizing COVID-19 care; ethical or not ethical? - Ramphul, Kamleshun; Lohana, Petras; Lohana, Arti; Kumar, Nomesh; Verma, Renuka (Acta Biomedica Atenei Parmensis, 2022)
-